Transition from Conventional to Sharia Methods for Recognizing PT. Nafa Berkah Mulia's Profitability - Istiarofah, Risma; Mulyaningtyas (GoAcademica Research & Publishing, 2025)
This study aims to analyze the impact of the transition from conventional accounting methods to sharia methods on profitability recognition at PT. Nafa Berkah Mulia, a manufacturing company in Indonesia. The study used a qualitative case study approach with data collection techniques in the form of observation, in-depth interviews, and documentation studies. Data analysis was carried out using data reduction, data presentation, and drawing conclusions. Data validity was tested through source triangulation and member checking. The results of the study indicate that the implementation of sharia principles has an impact on the financing structure, revenue recording methods, and the reformulation of business contracts. This transition presents several challenges, such as limited human resources who understand sharia accounting and an unprepared accounting information system. However, supporting factors such as management commitment, education on Islamic values, and guidance from sharia consultants contributed to the smoothness of the transformation process. In conclusion, this method shift can improve financial governance that is more in accordance with sharia and maintain sustainable profitability.